2020
DOI: 10.1002/prp2.587
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal epinephrine in dogs: Pharmacokinetic and heart rate effects

Abstract: Epinephrine is the standard of care for the treatment of severe allergy and anaphylaxis. Epinephrine is most often administered through the intramuscular (IM) route via autoinjector. The current study aimed to evaluate an alternative method of epinephrine treatment through intranasal (IN) delivery in dogs. The pharmacokinetic (PK) parameters of maximum plasma concentration (Cmax), time to reach maximum plasma concentration (Tmax), and area under the plasma concentration‐time curve from 0 to 90 minutes (AUC0–90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, drugs administered by the nasal route can directly reach the central nervous system (CNS) via the trigeminal and olfactory nerves (Erdo et al, 2018). The IN route of administration in dogs has been investigated for midazolam, dexmedetomidine, epinephrine, naloxone, and ketamine (Bleske et al, 1992; Charalambous et al, 2017; Charalambous et al, 2019; Dretchen et al, 2020; Santangelo et al, 2019; Tuttle et al, 2020; Vlerick et al, 2020; Wahler et al, 2019). These studies reported the intranasal route of administration to be clinically effective and/or results in adequate plasma concentrations of the investigated drug.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, drugs administered by the nasal route can directly reach the central nervous system (CNS) via the trigeminal and olfactory nerves (Erdo et al, 2018). The IN route of administration in dogs has been investigated for midazolam, dexmedetomidine, epinephrine, naloxone, and ketamine (Bleske et al, 1992; Charalambous et al, 2017; Charalambous et al, 2019; Dretchen et al, 2020; Santangelo et al, 2019; Tuttle et al, 2020; Vlerick et al, 2020; Wahler et al, 2019). These studies reported the intranasal route of administration to be clinically effective and/or results in adequate plasma concentrations of the investigated drug.…”
Section: Introductionmentioning
confidence: 99%